Responding to aid volatility: government spending on district health care in Zambia 2006–2017. Issue 1 (31st December 2020) - Jackson, Amy; Forsberg, Birger; Chansa, Collins; Sundewall, Jesper
ABSTRACT: Background : A corruption event in 2009 led to changes in how donors supported the Zambian health system. Donor funding was withdrawn from the district basket mechanism, originally designed to pool donor and government financing for primary care. The withdrawal of these funds from the pooled financing mechanism raised questions from Government and donors regarding the impact on primary care financing during this period of aid volatility. Objectives : To examine the budgets and actual expenditure allocated from central Government to the district level, for health, in Zambia from 2006 to 2017 and determine trends in funding for primary care. Methods : Financial data were extracted from Government documents and adjusted for inflation. Budget and expenditure for the district level over the period 2006 to 2017 were disaggregated by programmatic area for analysis. Results : Despite the withdrawal of donor funding from the district basket after 2009, funding for primary care allocated to the district level more than doubled from 2006 to 2017. However, human resources accounted for this increase. The operational grant, on the other hand, declined. Conclusion : The increase in the budget allocated to primary care could be an example of 'reverse fungibility', whereby Government accounted for the gap left by donors. However, the decline in the operational grant demonstrates that this period of aid volatility continued to have an impact on how primary care was planned and financed, with less flexible budget lines most affected during this period. Going forward, Government and donors must consider how funding is allocated to ensure that primary care is resilient to aid volatility; and that the principles of aid effectiveness are prioritised to continue to provide primary health care and progress towards achieving health for all.